2015
DOI: 10.1111/pce.12509
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of pigment and physiologically related photochemical reflectance index variability at the canopy scale over an entire growing season

Abstract: The sensitivity of the photochemical reflectance index (PRI) to leaf pigmentation and its impacts on its potential as a proxy for light-use efficiency (LUE) have recently been shown to be problematic at the leaf scale. Most leaf-to-leaf and seasonal variability can be explained by such a confounding effect. This study relies on the analysis of PRI light curves that were generated at the canopy scale under natural conditions to derive a precise deconvolution of pigment-related and physiologically related variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…Median R 2 (0.79 and 0.65, respectively; Figure 7d) was 7.0% and 4.0% higher for broadleaved and coniferous trees, respectively, than those (R 2 =0 .72 and 0.61, respectively) in Figure 5 in Garbulsky et al [20]. PRI accounted for 66% of the variability of RUE over an entire growing season for a mixed forest [107]. Four articles published after 2010 illustrated that PRI was strongly correlated with changes in net CO2 uptake for broadleaved (R 2 = 0.59 and 0.75) and herbaceous/crop (R 2 = 0.54 and 0.81) plants (Figure 7e).…”
Section: Seasonal Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Median R 2 (0.79 and 0.65, respectively; Figure 7d) was 7.0% and 4.0% higher for broadleaved and coniferous trees, respectively, than those (R 2 =0 .72 and 0.61, respectively) in Figure 5 in Garbulsky et al [20]. PRI accounted for 66% of the variability of RUE over an entire growing season for a mixed forest [107]. Four articles published after 2010 illustrated that PRI was strongly correlated with changes in net CO2 uptake for broadleaved (R 2 = 0.59 and 0.75) and herbaceous/crop (R 2 = 0.54 and 0.81) plants (Figure 7e).…”
Section: Seasonal Changesmentioning
confidence: 99%
“…Recent studies have indicated that the changes in the patterns of seasonal and inter-annual PRI were correlated with chlorophyllic and carotenoid pool sizes and structural properties [76,107,123,124]. Structural changes of the canopy caused by sustained water stress [120,123,125,126] or a varying leaf area index (LAI) [127] over the season led to PRI variability and loss of the seasonal relationship between PRI and RUE.…”
Section: Canopy Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate modelling between sunlit and shaded portions of canopy yielding different Chla+b/Carx+c and PRI was the most efficient way to simulate daily photosynthesis from multi-angular PRI measurements [81]. Contrary to the direct use of PRI, recent pioneering studies employing procedures to estimate ∆PRI from PRI 0 and PRI are leading to attempts to use ∆PRI for the purpose of estimating various stresses [25,75,78]. We also suggest that ability to discern between the two effects of Chla+b/Carx+c and daily dynamics in xanthophylls in PRI 0 should play a crucial role in evaluating ∆PRI.…”
Section: Evaluation Of Water Limitation From Primentioning
confidence: 99%
“…Similarly, Rippullone et al [77] tracked the photosynthetic responses of various tree species using ∆PRI under varying conditions of water stress. Hmimina et al [25] used ∆PRI to detect changes in LUE induced by water limitation in oak, beech, and pine saplings. Zhang et al [78] used ∆PRI to track photosynthesis responses to experimental drought and warming in a Mediterranean shrubland.…”
Section: Evaluation Of Water Limitation From Primentioning
confidence: 99%